2011
DOI: 10.1139/o11-063
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia acts through multiple signaling pathways to induce metallothionein transactivation by the metal-responsive transcription factor-1 (MTF-1)

Abstract: Metal-responsive transcription factor-1 (MTF-1) is essential for the induction of genes encoding metallothionein by metals and hypoxia. Here, we studied the mechanism controlling the activation of MTF-1 by hypoxia. Hypoxia activation of Mt gene transcription is dependent on the presence of metal regulatory elements (MREs) in the promoter of Mt genes. We showed that MREa and MREd are the main elements controlling mouse Mt-1 gene induction by hypoxia. Transfection experiments in Mtf-1-null cells showed that MTF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
(78 reference statements)
1
13
0
Order By: Relevance
“…Previously, we reported that P35 as well as Sb35 and As35 induce the expression of endothelial MT-2A by activating MRE (Fujie et al, 2016c). Therefore, our present and previous data suggest that Sb35 and As35 activate MTF-1, leading to the activation of MREs in the promoter region of MT, whereas P35 also activates the MREs by transcriptional factor(s) other than MTF-1 such as hypoxia inducible factor-1α (Dubé et al, 2011). As a result, these organopnictogen compounds induce the expression of MT-2A in vascular endothelial cells.…”
Section: Resultssupporting
confidence: 69%
“…Previously, we reported that P35 as well as Sb35 and As35 induce the expression of endothelial MT-2A by activating MRE (Fujie et al, 2016c). Therefore, our present and previous data suggest that Sb35 and As35 activate MTF-1, leading to the activation of MREs in the promoter region of MT, whereas P35 also activates the MREs by transcriptional factor(s) other than MTF-1 such as hypoxia inducible factor-1α (Dubé et al, 2011). As a result, these organopnictogen compounds induce the expression of MT-2A in vascular endothelial cells.…”
Section: Resultssupporting
confidence: 69%
“…The LUC reporter plasmid MT1-LUC contains 1843 bp of the 5= flanking region and 68 bp of the 5= untranslated region from the mouse Mt1 gene (Faraonio et al 2000). Similarly, the plasmid MT2A-LUC contains a human Mt2A gene DNA fragment (positions -780 to +65) cloned into pGL2 basic (Promega, Madison, Wisconsin, USA) (Dubé et al 2011). To construct plasmid (MREd) 6 -LUC, a synthetic DNA fragment containing 6 mouse Mt1 MREd elements (Labbé et al 1991) (5 elements in direct tandem orientation and the 6th in the opposite orientation) was cloned in front of a minimal mouse Mt1 promoter DNA fragment (positions -35 to -68) into the LUC reporter plasmid pGL2-Basic (Promega, Madison, Wis.).…”
Section: Reagents and Plasmid Constructsmentioning
confidence: 99%
“…Metal exposures were done with cadmium or zinc with the dose strengths of 20 and 100 ppb for 24 h. RT-qPCR data were presented as fold changes of MTF-1 mRNAs in expressed groups relative to that of non-exposed control (Con) based on the normalization against two internal control genes (RPL5 and PPL7). Histograms with different letters indicate the significantly different means based on ANOVA followed by Duncan's multiple ranged tests at P < 0.05 (Dubé et al 2011;Cheuk et al 2008) and carp (Ferencz and Hermesz 2009), which is obviously different from the principle for the MTF-1 regulation in mammals (Bi et al 2006;Saydam et al 2001).…”
Section: Expression During Zn and CD Exposurementioning
confidence: 90%
“…Besides, several transcription factor binding sites such as heat shock element (HSE; GAANRTTC; −1003 and −32 bp; targeted by heat shock factor (HSF)), hypoxia response element (HRE; RCGTG; −895 and −285 bp; by hypoxiainducible factor-1 alpha (HIF-1α)), and other sites recognized by cyclic AMP response element binding protein (CREBP; TGACGY; −1253 bp) and nuclear factor for activated T-cells (NF-AT1; WGGAAA; −941, −169, and −33 bp) were predicted. All of these factors have been known to be related with stress responses of animals (Saydam et al 2003;Dubé et al 2011). Abalone MTF-1 promoter also revealed motifs that might be targeted by transcription factors generally known to be involved in development, signal transduction, cell proliferation and/or organ development.…”
Section: Prediction Of Transcription Factor Binding Sitesmentioning
confidence: 99%